Genetic diversity and relationships among native Japanese horse breeds, the Japanese Thoroughbred and horses outside of Japan using genome‐wide SNP data. (8th July 2019) - Tozaki, T.; Kikuchi, M.; Kakoi, H.; Hirota, K.; Nagata, S.; Yamashita, D.; Ohnuma, T.; Takasu, M.; Kobayashi, I.; Hobo, S.; Manglai, D.; Petersen, J. L.
Summary: Eight horse breeds—Hokkaido, Kiso, Misaki, Noma, Taishu, Tokara, Miyako and Yonaguni—are native to Japan. Although Japanese native breeds are believed to have originated from ancient Mongolian horses imported from the Korean Peninsula, the phylogenetic relationships among these breeds are not well elucidated. In the present study, we compared genetic diversity among 32 international horse breeds previously evaluated by the Equine Genetic Diversity Consortium, the eight Japanese native breeds and Japanese Thoroughbreds using genome‐wide SNP genotype data. The proportion of polymorphic loci and expected heterozygosity showed that the native Japanese breeds, with the exception of the Hokkaido, have relatively low diversity compared to the other breeds sampled. Phylogenetic and cluster analyses demonstrated relationships among the breeds that largely reflect their geographic distribution in Japan. Based on these data, we suggest that Japanese horses originated from Mongolian horses migrating through the Korean Peninsula. The Japanese Thoroughbreds were distinct from the native breeds, and although they maintain similar overall diversity as Thoroughbreds from outside Japan, they also show evidence of uniqueness relative to the other Thoroughbred samples. This is the first study to place the eight native Japanese breeds and Japanese Thoroughbred in context with an international sample of diverse breeds.